Determinación y clasificación de residuos de la construcción para Condominio Horizontal - Salas-Camacho, Erika; Quesada-Aguilar, Elías (Instituto Tecnológico de Costa Rica, 2006)
This project focuses on the constructive process solid waste management, in the Fuerte Ventura condominium of Kirebe Real State Promotors Company, where the construction’s residues were identified, classified and it was established recommendations for its reuse, recycle and final destination. The research was about the best practices in construction solid waste management, and based on its results it was established the classification parameters. Once classified, it was done an analysis about this residues types of reuse and it was determined which ones could be recyclable. For these materials there were proposed a list of contacts for the nearest recycle centers. In addition, it was investigated about dangerous debris of construction and was recommended minimum thresholds for the regulation of this activity. Finally, it was generated a general manual for the management of debris on the different constructive activities identified in the project in study.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2006.
Keywords: Reutilización; Reciclaje; Residuos peligrosos